Peningkatan Softskill Guru Menggunakan Metode Microteaching Melalui Media Visual Sederhana Interaktif pada Majelis Dikdasmen PNF PDM Kota Sorong - Andi Maryam; Muh. Mawardi; Ainun Mardiyah; Rizky Ekawaty Ahmad; Jenro P. Sijabat; Abu Bakar; Irfandi Idris; Imelti Rerung; Al Mar Atu Soleha (Pusat Riset dan Inovasi Nasional, 2025)
Improving the quality of education in Indonesia requires continuous efforts to develop teachers' competencies, especially in soft skills related to pedagogical abilities and the use of technology in learning. This community service aims to enhance the soft skills of teachers in the Majelis Dikdasmen PNF PDM of Sorong City through the application of the microteaching method with simple interactive visual media. The microteaching method provides teachers with the opportunity to practice teaching in short sessions, which are then evaluated by peers and facilitators. Additionally, simple visual media such as PowerPoint, learning videos, and infographics are used to enrich the teaching and learning experience. This community service is conducted in the form of theory and practice sessions, followed by group discussions and reflections to strengthen participants' understanding. The results of the service show an improvement in teachers' ability to effectively use visual media, as well as an enhancement in their skills in managing classrooms interactively. This service is expected to significantly contribute to the professionalism of teachers in Sorong City, particularly in improving the quality of the teaching-learning process in non-formal education levels.